(untitled) (Journal of Asian Development Studies, 2026)
Pakistan is the country with more than 100 million children and spina bifida is a neural tube defect that commonly affects children. Folic acid deficiency during the initial three weeks of pregnancy has been identified as a significant causative factor. However, other factors and their effects vary based on geographic location, maternal pregnancy history, child sex, and race. This cross sectional study aimed to investigate the factors contributing to the incidence rate of spina bifida in Lahore, Pakistan. A total of 200 cases of neural tube defects, including spina bifida, were studied and reported from October 2012 to August 2013 at Children’s Hospital Lahore. Various factors were examined, such as the age of mothers, with 50% of babies with neural tube defects born to mothers aged between 26 and 36 years. The incidence of spina bifida was found to be higher in boys (59%) compared to girls (41%). Hydrocephalus, a common complication of spina bifida, was more prevalent in boys (51%) than in girls (14%). Spina bifida cystica, another form of the condition, occurred more frequently in girls (38%) than in boys (33%). In this study group, 161 out of 200 women did not use or properly use folic acid during pregnancy, indicating a lack of awareness regarding its importance. The study also revealed that 119 cases of spina bifida occurred during winter, suggesting a seasonal influence on the condition. In addition to other identified risk factors, this study underscores the critical need for raising awareness about the use of folic acid before conception and during the initial three weeks of pregnancy.